TGF-β1 and its association with clinicopathological features, proliferative activity and prognosis in oral squamous cell carcinoma: An immunohistochemical study - Weissheimer, Camila; Wagner, Vivian Petersen; Webber, Liana Preto; Sant’Ana Filho, Manoel; dos Santos, Jean Nunes; Martins, Manoela; Meurer, Luise; Martins, Marco Antônio Trevizani (Clinical and Biomedical Research, 2019)
Introduction: The prognostic value of transforming growth factor beta-1 (TGF-ß1) in oral cancer remains unclear. Therefore, the aim of this study was to evaluate TGF-β1 expression in oral squamous cell carcinoma (OSCC) samples and its association with clinicopathological data, tumor proliferative activity and patients’ prognosis. Methods: Sixty-eight patients with histopathological diagnosis of OSCC were included, as 9 cases of normal oral mucosa for comparison purposes. OSCC sample was categorized according to patients’ outcomes in favorable prognosis (n=30) or unfavorable prognosis (n=38). Immunohistochemical staining for TGF-β1 and Ki-67 was performed. The slides were semi-quantitatively and quantitatively evaluated for TGF-β1 and Ki-67, respectively. Results: TGF-β1 was significantly increased in OSCC compared to normal oral mucosa (<0.01). An inverse correlation was found between TGF-β1 and Ki67 staining in OSCC (p=0.01). No association was found between TGF-β1 expression and OSCC clinicopathological features, prognosis or survival. Conclusion: TGF-β1 had no prognostic value and appears to maintain it’s suppressive role concerning cell proliferation. Keywords: Head and neck neoplasms; prognosis; transforming growth factors